2016
DOI: 10.1371/journal.pone.0166223
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Intracerebral Hemorrhage: Associations with Comorbidities and Medicine with Antithrombotic Effects

Abstract: BackgroundIntracerebral hemorrhage (ICH) is a disease with high mortality and a substantial risk of recurrence. However, the recurrence risk is poorly documented and the knowledge of potential predictors for recurrence among co-morbidities and medicine with antithrombotic effect is limited.Objectives1) To estimate the short- and long-term cumulative risks of recurrent intracerebral hemorrhage (ICH). 2) To investigate associations between typical comorbid diseases, surgical treatment, use of medicine with antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…This is consistent with a few previous studies that were conducted on patients with ICH that found that recurrence of ICH increases with time of follow up. 61,62 A review by Endres and colleagues summarized the studies that investigated statin use and ICH recurrence and concluded that there is no evidence that statin increased risk of ICH recurrence. 63…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a few previous studies that were conducted on patients with ICH that found that recurrence of ICH increases with time of follow up. 61,62 A review by Endres and colleagues summarized the studies that investigated statin use and ICH recurrence and concluded that there is no evidence that statin increased risk of ICH recurrence. 63…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies of chronic antiplatelet use after ICH have hitherto mainly focused on ICH recurrence risk. [5][6][7][8][9][10][11] It is unclear how use of antiplatelets after HS influences long-term overall mortality irrespective of use before HS. This is of particular interest since patients on antiplatelet drugs might discontinue this therapy after suffering an ICH; further, patients with both ICH 12,13 and SAH [14][15][16] are reported to be at increased long-term risk of mortality due to cardiovascular and cerebrovascular events other than recurrence of the index event.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis reported an annual risk of recurrence after spontaneous ICH between 1.3-7.4%, but most of these studies started follow-up at 30 or 90 days after the hemorrhage. 238 One recent study investigating recurrence up to 5 years after primary ICH reported the cumulative recurrence risk of ICH after 28 days being 3.67% (95% CI 3.37-3.97), 239 which is comparable to many ischemic stroke studies.…”
Section: Discussionmentioning
confidence: 64%